Analisis Kelembagaan Badan Wakaf Indonesia - Rahmat Dahlan (Faculty of Economic and Business, 2016)
Organizational Analysis of Indonesian Waqf BoardThe emergence of the idea of ​​cash waqf is surprising to many people, especially experts and practitioners of Islamic economics. The method used in this research is a normative legal research method (legal research). One of the objectives the need to establish Indonesian Waqf Board is to promote and develop waqf. Indonesian Waqf Board plays an active role as a regulator, motivator, mediator, and also can play a role as the administrator of waqf itself (nazhir). Therefore, it is in the case of appointment Indonesian Waqf Board membership management needs are called upon with some requirements such as having the vision and mission of commitment to develop waqf, has a working knowledge of and experience in managing waqf assets in a professional manner on a national scale.DOI: 10.15408/ess.v6i1.3125